2006
DOI: 10.1016/j.dss.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of internet banking: An empirical study in Hong Kong

Abstract: This study investigates how customers perceive and adopt Internet Banking (IB) in Hong Kong. We developed a theoretical model based on the Technology Acceptance Model (TAM) with an added construct Perceived Web Security, and empirically tested its ability in predicting customers' behavioral intention of adopting IB. We designed a questionnaire and used it to survey a randomly selected sample of customers of IB from the Yellow Pages, and obtained 203 usable responses. We analyzed the data using Structured Equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
394
4
19

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(524 citation statements)
references
References 31 publications
37
394
4
19
Order By: Relevance
“…The results showed that the users' perceived ease of use of the box lunch ordering system platform would significantly influence the perceived usefulness and would indirectly affect usage attitudes through the perceived usefulness, while the perceived usefulness would also directly affect usage attitudes. In the single model, the TAM's usefulness and ease of use are the factors that affect usage attitudes, and the usage attitude is the antecedent variables for the usage behavioral intentions, which is consistent with past researches (Davis et al, 1989;Patrick, 1996;Igbaria and Tan, 1997;Venkatesh and Davis, 2000;Lin and Lu, 2000;Moon and Kim, 2001;Wu, 2001;Chen et al, 2002;Shih, 2004;Yen, 2005;Vijayasarathy, 2004;Shang et al, 2005;Cheng, Lam and Yeung, 2006;Porter and Donthu, 2006;King and He, 2006;Schepers and Wetzels, 2007;Chang, 2007). However, usefulness does not have a significant influence on usage behavioral intentions, which differs from the TAM model.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The results showed that the users' perceived ease of use of the box lunch ordering system platform would significantly influence the perceived usefulness and would indirectly affect usage attitudes through the perceived usefulness, while the perceived usefulness would also directly affect usage attitudes. In the single model, the TAM's usefulness and ease of use are the factors that affect usage attitudes, and the usage attitude is the antecedent variables for the usage behavioral intentions, which is consistent with past researches (Davis et al, 1989;Patrick, 1996;Igbaria and Tan, 1997;Venkatesh and Davis, 2000;Lin and Lu, 2000;Moon and Kim, 2001;Wu, 2001;Chen et al, 2002;Shih, 2004;Yen, 2005;Vijayasarathy, 2004;Shang et al, 2005;Cheng, Lam and Yeung, 2006;Porter and Donthu, 2006;King and He, 2006;Schepers and Wetzels, 2007;Chang, 2007). However, usefulness does not have a significant influence on usage behavioral intentions, which differs from the TAM model.…”
Section: Resultssupporting
confidence: 60%
“…Davis's (1989) exploration of the student usage of word processing tools in TAM has been confirmed. Lin and Lu (2000) explored the usage of Internet web pages, and the empirical results showed that there is a positive correlation between the perceived ease of use and the perceived usefulness, and that the perceived usefulness also has a positive correlation to usage intentions (Cheng, Lam and Yeung, 2006;Porter and Donthu, 2006;Chu, Huang and Weng, 2008;Wu, Chu and Fang, 2008;Chen, Shang and Liu, 2010;Chen and Liu, 2010). Shih (2004) found that the perceived ease of use has a more significant effect on Internet usage attitudes than the perceived usefulness, and that the perceived ease of use has a positive correlation to the perceived usefulness.…”
Section: Technology Acceptance Modelmentioning
confidence: 99%
“…Criticism: Despite the robustness of TAM, the model have also been found to possess some limitations in its application to consumer adoption of the electronic marketing applications and several authors have extended TAM (Pikkarainen et al, 2004;Lee, 2009) or supplemented it by combining it with other factors (Cheng et al, 2006). Moreover, TAM's lack of explanatory power in the context of consumer adoption might have accounted for its failure to account for differences in the prior experience of users.…”
Section: Theoretical Underpinning: Technological Acceptance Model (Tam)mentioning
confidence: 99%
“…Correspondingly, Davis (1989) introduced the construct TAM as follow: perceived usefulness (PU), perceived ease of use (PEOU), attitude and behavioural intention to use. Among the constructs, PU and PEOU form an end-user's beliefs on a technology and therefore predict his or her attitude towards the technology, which in turn predicts its acceptance (Cheng, Lam & Yeung, 2006). Various authors, simply posits that individuals who are keen to adopt an innovation, would want to believe or made to believe that they will not find a particular technology difficult to use and it would require no much labour in is usage.…”
Section: Theoretical Underpinning: Technological Acceptance Model (Tam)mentioning
confidence: 99%